Grandmother and mother relationship for rearing the first child - Servado, Karla Theresa R.; Uy, Bless Anne N. (College of Home Economics, University of the Philippines Diliman, 2021)
This study seeks to describe the relationship of Filipino grandmothers and mothers focusing on their shared values and usual topics of communication in child-rearing the first grandchild. The roles of the grandmother to the mother as she rears her first child will also be identified. Through purposive sampling, ten pairs of related grandmothers and mothers from the National Capital Region will be selected to participate in the study. This qualitative descriptive research will gather data through separate interviews followed by a paired interview. The purpose of separate interviews among grandmothers and mothers will allow the gathering of data from individual perspectives and experiences of the respondents. Through a paired interview, an in-depth view of the relationship can be described by both the perspectives of the grandmother and mother with an opportunity for the respondents to report in detail their experiences. The collected information and data will then be compiled and organized into specific categories or themes. These findings may provide an understanding of the relationship between Filipino grandmothers and mothers particularly their shared values, topic of communication, and roles in the context of rearing the first child. In result, Filipino grandmother and mother dyads may modify and improve their communication, dynamics, and relationship.